2018
DOI: 10.3389/fimmu.2018.01889
|View full text |Cite
|
Sign up to set email alerts
|

Thymopoiesis in Pre- and Post-Hematopoietic Stem Cell Transplantation

Abstract: Hematopoietic stem cell transplantation (HSCT) is an important therapeutic option for some hematological diseases. However, patients who undergo HSCT acquire a state of immunodeficiency that causes significant mortality. Reconstitution of thymic function is needed to support the immune system. One way to measure thymic function is through T-cell receptor excision circle (TREC) quantification. TRECs are generated by T-cell receptor gene rearrangements during T-cell maturation in the thymus and represent a relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Remarkably, since RANKL is the master gene of osteoclastogenesis, it is tempting to speculate that the increased osteoclast activity may also boost hematopoiesis and consequent migration of thymic progenitors. Overall, these in vivo findings confirm the therapeutic effect of RANKL suggesting its putative use to boost immune reconstitution in transplanted elderly patients or in patients affected by primary thymic epithelial defects (104106) (Figure 1D). Conversely, transient inhibition of RANKL in murine models indicate its effect on thymic negative selection of self-reactive T cells specific for tumor antigens, and resulting in an improvement of antitumor immune response (107, 108).…”
Section: Rankl-rank Axis In the Thymussupporting
confidence: 71%
“…Remarkably, since RANKL is the master gene of osteoclastogenesis, it is tempting to speculate that the increased osteoclast activity may also boost hematopoiesis and consequent migration of thymic progenitors. Overall, these in vivo findings confirm the therapeutic effect of RANKL suggesting its putative use to boost immune reconstitution in transplanted elderly patients or in patients affected by primary thymic epithelial defects (104106) (Figure 1D). Conversely, transient inhibition of RANKL in murine models indicate its effect on thymic negative selection of self-reactive T cells specific for tumor antigens, and resulting in an improvement of antitumor immune response (107, 108).…”
Section: Rankl-rank Axis In the Thymussupporting
confidence: 71%
“…These findings are in accordance with the observations published by Clave, Lisini et al, who described a group of 57 patients transplanted for either malignant or non-malignant diseases, and before transplantation TREC values were significantly lower in the 46 patients with hematological malignancies than in the 11 with non-malignant disorders [20]. Other studies confirmed that hematologic malignancies and chemotherapy are important and independent risk factors related to thymic inhibition [21][22][23]. Petridou et al published a study of 120 patients (30 with T-cell leukemia/non-Hodgkin's lymphoma, 30 age-and sexmatched with B-cell ALL and 60 healthy hospital controls) and reported that in a group with T-cell malignancies a reduction of TREC values was noted whereas in children with B-cell ALL only slightly and non-significantly lower TREC values were observed compared to healthy children controls [24].…”
Section: Underlying Diseasesupporting
confidence: 91%
“…CMV directly invades the thymus, causing disruption of its architecture, degradation of the thymic microenvironment and poor immune recovery after HSCT [33]. Toubert et al and Klaus da Rocha et al found an association between poor thymic recovery and a higher incidence of CMV reactivation in allo-HSCT patients [14,23]. Also results published by Lewin et al showed that low TREC levels were significantly correlated with severe opportunistic infections [34].…”
Section: Viral Reactivationsmentioning
confidence: 99%
“…This is contradictory to most of the published data, which report significantly lower levels of TRECs in patients who develop infections [35]. In a study by da Rocha et al [36] a 3-fold lower risk of developing severe infections was observed in those patients who had effective sjTREC+ T-cell recovery at 6 months, and a 9-fold lower risk at 12 months. In another study, lower TREC levels at 9 months were related to CMV episodes, but not to other infections [36].…”
Section: Discussionmentioning
confidence: 68%